Enhancing Productivity of Passive Solar Still Using Black Cylindrical Fins - Mohd Zahid, Puteri Nor Atikhah Fadhilah (IRC, 2016)
There is limited access to clean drinking water that meets standard limits of water quality, especially in the rural areas. Approximately 1.2 billion people around the world lack access to clean drinking water and among these people there are 82% live in rural areas and 18% live in urban areas. Passive solar stills, structures relying on the sun’s power as one of the most promising alternatives is the key to solve this problem. The quality of water there can be improved through solar distillation using solar power that is available all around the world. It has the potential to become a low-tech alternative and also inexpensive way of producing drinking water. The conventional passive solar still is widely exploited but it has low productivity. The objective of this research was to overcome these limitations. There were three sets of passive solar still used in this research; conventional solar still (SSC), solar still using black basin (SSB) and solar still using black basin incorporated with 28 pieces of black cylindrical basin (SSBF). The average daily cumulative yield of SSBF is 2.71 L/m2 while SSB produced only 2.03 L/m2 and SSC produced 1.46 L/m2. It is found that the SSBF increases the productivity of passive solar still by 86% if compared to SSC and 33% if compared to SSB. Keywords - Solar Distillation, Passive Solar Still, Cylindrical Fin Heating